Impact of bisphosphonate drug burden in alveolar bone during orthodontic tooth movement in a rat model: A pilot study - Kaipatur, N.; Wu, Y.; Adeeb, S.r; Stevenson, T.; Major, P.; Doschak, Michael (Mosby, Inc., 2013)
INTRODUCTION: The aim of this pilot study was to investigate the effect of long-term bisphosphonate drug use (bone burden) on orthodontic tooth movement in a rat model. METHODS: Sprague Dawley rats were used for orthodontic protraction of the maxillary first molars with nickel-titanium coil springs and temporary anchorage devices as anchorage. Four groups of 5 rats each were included in the study; the first 2 groups were dosed with alendronate or a vehicle during concurrent orthodontic tooth movement. The third and fourth groups were pretreated for 3 months with alendronate or vehicle injections, and bisphosphonate drug treatment was discontinued before orthodontic tooth movement. Tooth movement measurements were obtained at 0, 4, and 8 weeks using high-resolution in-vivo microcomputed tomography, and the tissues were analyzed with histology and dynamic labeling of bone turnover. RESULTS: Appreciable tooth movement was achieved during the 8-week duration of this study with nickel-titanium coil springs and temporary anchorage devices. Both bisphosphonate treatment groups exhibited reduced tooth movement compared with the vehicle-dosed controls with a tendency toward more severe reduction in the bisphosphonate predosed group. Concurrent dosing of the bisphosphonate drug resulted in 56% and 65% reductions in tooth protraction at the 4-week and 8-week times, respectively. The impact of bisphosphonate bone burden in retarding tooth movement was even greater, with 77% and 86% reductions in tooth movement at 4 and 8 weeks, respectively. CONCLUSIONS: In this study, we used a robust rat model of orthodontic tooth movement with temporary anchorage devices. It has provided evidence that the bone burden of previous bisphosphonate use will significantly inhibit orthodontic tooth movement.